Risk Factors Associated with the Incidence of Stunting in Toddlers Aged 6-24 Months - Hasan, Amrul; Kadarusman, Haris; Sutopo, Agus (Jurnal Kesehatan, 2023)
The high stunting in toddlers aged 6-24 months is due to low access to quality drinking water, sanitation, and hygiene. Therefore, the risk of toddlers suffering from infectious diseases is still high, which disrupts the intake of nutrients needed for toddler growth. North Lampung Regency is one of the districts with a priority for tackling stunting because it still has a stunting prevalence of 24.7%. This study aims to determine risk factors associated with stunting, using a case-control design, a total sample of 768 (384 cases, 384 controls) toddlers 6-24 months in 39 villages from eight sub-districts. The study found that a history of exclusive breastfeeding is associated with stunting, OR=1,90 (95%CI: 1,36-2,65. History of sick children is related to the stunting at risk with OR=2,48 (95%CI: 1,70-3,62). Family income